2022
DOI: 10.1111/wej.12781
|View full text |Cite
|
Sign up to set email alerts
|

Urban households' willingness to pay for improvements in rainwater harvesting and rainwater infiltration system: Case study in Japan

Abstract: There is an urgent need to develop an urban rainwater drainage system in cities that have been facing flooding due to heavy rainfall events. In Japan, many municipalities have provided financial support for installing household‐level rainwater infiltration and harvesting facilities. However, the use of domestic installations is still limited. This study used the contingent valuation method (CVM) to investigate household preferences for rainwater tanks and a rainwater infiltration inlet (RII) in Yokohama, Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Therefore, it is necessary to study how to increase the social acceptability of this policy and how the budget for this policy is appropriately set. In Table 8, according to Model 1-2 and 2-2 considering covariates, experience of damage from extreme weather and WTP for climate change adaptation measures showed a positive relationship, at 0.642548 and 0.662593, respectively, which is supported by a previous study from Singapore 18,21 which showed that the WTP of the residents with the highest urban heat island intensity was 3.09 times higher than that of the residents with the lowest intensity. Secondly, the interest in climate change and WTP for climate change adaptation measures also showed a positive relationship at 0.341204 and 0.295596, respectively, which is supported by previous studies from Malaysia 15 and Singapore.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Therefore, it is necessary to study how to increase the social acceptability of this policy and how the budget for this policy is appropriately set. In Table 8, according to Model 1-2 and 2-2 considering covariates, experience of damage from extreme weather and WTP for climate change adaptation measures showed a positive relationship, at 0.642548 and 0.662593, respectively, which is supported by a previous study from Singapore 18,21 which showed that the WTP of the residents with the highest urban heat island intensity was 3.09 times higher than that of the residents with the lowest intensity. Secondly, the interest in climate change and WTP for climate change adaptation measures also showed a positive relationship at 0.341204 and 0.295596, respectively, which is supported by previous studies from Malaysia 15 and Singapore.…”
Section: Discussionsupporting
confidence: 72%
“…21 Finally, the relationship between income and WTP for climate change adaptation measures was also positive, at 0.081157 and 0.080569, respectively, in line with previous studies conducted in Pakistan, 13 Malaysia, 14,15 Iran, 16 Singapore, 21 Bangladesh, 19 Germany, 16 and Japan. 18 Furthermore, as a long-term strategy, based on not only this result but also a positive relationship found between annual income and social media usage rate, 40 we proposed to use social media as a means of policy promotion, including the dissipation of knowledge on the scientific basis of climate change adaptation policy and overseas trends. While the rate of awareness regarding the NCCAP was less than 50% (Table 4), the relationship between the awareness of the establishment and implementation of the NCCAP and WTP was positive, at 0.657105 and 0.553524, respectively (Table 8), which implies that it is necessary to allow people to participate in the policy formulation process on a large scale rather than going for top-down education and publicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings align with previous studies. For example, a case study in Japan indicated that respondents had a high interest and were willing to pay for improvements in rainwater harvesting and rainwater infiltration system, which could be attributed to the intuitive and easily comprehensible benefits of installing rainwater tanks [48]. In our study, residents' intuitive perception of the degree of ponding was influenced by walking through on water splashes on the road surface, and which had a noticeable and intuitive impact.…”
Section: Degrees Of Pondingmentioning
confidence: 60%